Low 25-Hydroxyvitamin D is associated with increased mortality in female nursing home residents - Pilz, Stefan; März, Winfried (The journal of clinical endocrinology & metabolism, 2012)
Context:. Vitamin D deficiency contributes to skeletal diseases and is highly prevalent among institutionalized elderly patients. Whether low 25-hydroxyvitamin